Climate-Smart Agriculture in Sinaloa, Mexico - Zavariz-Romero, Beatriz; Cervantes, C; Nowak, Andreea C.; Lizarazo, Miguel; Imbach, Pablo; Halliday, Andrew; Prasodjo, Rauf; Baca, María; Medellín, Claudia; Argote, Karolina; Zamora, Juan Carlos; Louman, Bastian; et al. (World Bank, 2014)
The climate-smart agriculture (CSA) concept reflects an ambition to improve the integration of agriculture development and climate responsiveness. It aims to achieve food security and broader development goals under a changing climate and increasing food demand.